The Influence of Brand Image, Price, and Product Quality on Purchase Decisions to iPhone Products in Bandar Lampung - Cindy; Desi Derina Yusda; Umar Bakti (FEB - Universitas Lampung, 2024)
ABSTRACT This research aims to determine the influence of brand image , price and product quality variables on iPhone product purchasing decisions either separately (partial) or together (simultaneous) and to find out which brand image , price and product quality variables play a more important role. in influencing iPhone product purchasing decisions . The research data collection technique was carried out by observing and distributing questionnaires directly by visiting the research object and distributing the questionnaire link, namely to consumers who had made the decision to purchase an iPhone . The collected data is then tabulated and processed using multiple regression analysis. The research results show that the price and product quality variables have a significant effect on purchasing decisions. Meanwhile, the brand image variable does not have a significant effect. The dominant variable that has an influence is product quality. Keywords : Brand Image , Price, Product Quality, Purchasing Decisions